The Role of Youtube in Building Brand Image Communication in Technology Review Content on the Gadgetin Channel (David Brandi) - Alwi Hanapi Harahap (Pena Cendekia Insani, 2020)
This research highlights the rapid development of informationtechnology which has given rise to a modern, all-digital life traditionin a number of fields. The use of the internet in the global era as aform of advances in digital technology towards the vision ofmodernization of information is now growing drastically, especiallyin terms of meeting the needs of the information community in thesocio-economic field. Viewed from the business side, the use of theinternet for online media which is usually called social media, one ofwhich is YouTube. Youtube is very profitable for market players,investors, or industry players. In accordance with the formulation ofthe problem above, the purpose of this study is to find out